Citra Pasangan Ideal dan Islami dalam Cerpen Lailatu az-Zifaf dan Cerpen Malam Perkawinan - Ranjy Ramadani (Alfaz (Arabic Literatures for Academic Zealots), 2020)
Abstract: This research is a comparative study between two short stories which have similar tittles but are written by authors of different gender and nationality. The two short stories are “Lailatu az-Zifaf” by Taufiq al-Hakim who is well-known Egyptian writer and “Malam Perkawinan” by Evi Idawati from Indonesia. The many similarities found in the stories make the writer interested to raise them in comparative literature study. Firstly, this two short stories are examined through Robert Stanton’s structural approach, then are analyzed through comparative approach to get the ideal islamic pair image found in the stories. The results of the study are in the short story “Lailatu az-ZIfaf”, Taufia al-Hakim gives equal portions between man and woman. The main figure, who are husband and wife, is described as having ideal characteristics in building the household. While the short story “Malam Perkawinan” describes the ideal figure desired by woman in a man.